Bahasa Inggris - Hanif, Hanif; Susilo, Joko; Basuki, Rizqy Aziz; Vittorio, Kevin Wilmer; Pramudya, Hans (Faculty of Economics and Business, Universitas Negeri Jakarta, 2025)
This community service program seeks to strengthen the capacity of Micro, Small, and Medium Enterprises (MSMEs) by implementing the Mato-Based Profit-Sharing Accounting System (ABHSM) through its integration into the digital application Inmato.ID. The methodological framework combined the System Development Life Cycle (SDLC), capacity building, and participatory action research (PAR), ensuring systematic system development as well as active involvement of partner enterprises. The program was conducted with MSMEs under the OK OCE initiative, supported by Rumah Makan Padang Simpang Raya as an industry partner. The findings reveal substantial outcomes: the partners’ accounting literacy increased from 40% to 78%, production cost deviation was reduced from approximately ±20% to ±8%, and profit distribution time shortened from 2–3 weeks to a maximum of 1 week. These results demonstrate that the digitalization of ABHSM enhances efficiency, accountability, and empowerment of MSMEs, while providing a replicable model for broader application across diverse business sectors in fostering sustainable entrepreneurial ecosystems.